2018
DOI: 10.15296/ijwhr.2018.78
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Effects of Acupressure and Electroacupuncture in Primary Dysmenorrhea: A Randomized Controlled Trial

Abstract: Introduction Dysmenorrhea is painful menstruation that usually accompanied by cramping that is felt in the lower abdomen. Dysmenorrhea is generally divided into 2 types of primary and secondary. Primary dysmenorrhea is a spasmodic pain that is associated with ovulatory cycles, in the absence of demonstrable pathology. Secondary dysmenorrhea is a congestive pain that is associated with organic uterine or pelvic pathology such as endometriosis, adenomyosis, myomas and so on (1). Dysmenorrhea can be accompanied b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 14 publications
(18 reference statements)
0
15
0
Order By: Relevance
“…The study with the largest number of participants had 194 individuals [10,11]. 1 study conducted electroacupuncture and acupressure [9], and 1 study compared the effects of electroacupuncture, general acupuncture, and oral analgesics [12]. 1 study compared EA and oral analgesics [13], and the other 3 studies also included comparisons of acupoints, unrelated acupoints, and non-acupoints [10,11,14].…”
Section: Overview Of Selected Studiesmentioning
confidence: 99%
See 3 more Smart Citations
“…The study with the largest number of participants had 194 individuals [10,11]. 1 study conducted electroacupuncture and acupressure [9], and 1 study compared the effects of electroacupuncture, general acupuncture, and oral analgesics [12]. 1 study compared EA and oral analgesics [13], and the other 3 studies also included comparisons of acupoints, unrelated acupoints, and non-acupoints [10,11,14].…”
Section: Overview Of Selected Studiesmentioning
confidence: 99%
“…Katayun et al [9] included female patients aged 18-26 years who had a definitive diagnosis of PD by their gynecologist and had regular menses for 2 years with a cycle between 28 ± 7 days. Song et al [10] reported on infertile females aged 15 to 30 years with a regular menstrual cycle (28 ± 7 days) who had been diagnosed with PD between 6 months and 15 years of the onset of symptoms, were according to the Canadian Association of Obstetricians and Gynecologists "Clinical Guidelines for Primary Dysmenorrhea" (2005).…”
Section: Overview Of Selected Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Significant differences between the intervention and follow-up phases were found for high frequency (HF. Penekanan pada titik akupresur dapat menstimulasi jaringan syaraf untuk melepaskan hormon endorfin sesuai kebutuhan tubuh (Qorbanalipour et al, 2018) complementary or surgical treatments. The aim of the present randomized clinical trial (RCT.…”
Section: Pembahasanmentioning
confidence: 99%